Sweep scan path planning for efficient freeform surface inspection on five-axis CMM. (August 2016) - Zhou, Zi; Zhang, Yang; Tang, Kai
Abstract: Compared with the traditional 3-axis coordinate measuring machine (CMM), a 5-axis CMM equipped with the capability of continues sweep scanning can provide much denser data points while taking much shorter time. This paper presents an automatic sweep scan path planning system that generates a continuous sweep scanning path for the inspection of an arbitrary free-form surface using a 5-axis CMM with three translational axes and a rotary head with two very light rotary axes. The system strives to significantly improve the scanning efficiency by utilizing the superb kinematic advantages of the two rotary axes, which have very low moment of inertia, to cover a larger area, while tremendously reducing the speed and acceleration demand on the three translational axes which have much larger inertia. The path is generated from a mesh model of the freeform surface and an iterative approach is used to ensure that the stylus contacts the surface at an acceptable angle during the entire scan. Physical scanning experiments are performed and the test results show significant improvement in scanning efficiency by the proposed sweep scan path planning method when compared with some existing continuous scanning path planning approaches such as the standard isoparametric or zigzag method. Highlights: A method for planning sweep scan path for freeform surfaces on a 5-axis CMM is proposed. The generated scan path utilizes kinematic advantages of 5-axis CMM to improve scanning efficiency. Experiments show significant improvement in scanning efficiency compared to some existing methods.